Predicting freshwater production and energy consumption in a seawater greenhouse based on ensemble frameworks using optimized multi-layer perceptron - Ehteram M.; Ahmed A.N.; Kumar P.; Sherif M.; El-Shafie A. (Elsevier Ltd, 2023)
Climate models; Decision making; Forecasting; Greenhouses; Mean square error; Particle swarm optimization (PSO); Seawater; Uncertainty analysis; Water supply; Average modeling; Bayesian; Copula bayesian average model; Decision makers; Energy-consumption; Ensemble models; Fresh Water; Freshwater production; Multilayers perceptrons; Optimization algorithms; Energy utilization